Eco‐evolutionary feedbacks among pollinators, herbivores, and their plant resources. (1st June 2022) - McPeek, Sarah J.; Bronstein, Judith L.; McPeek, Mark A.
Abstract: Eco‐evolutionary feedbacks among multiple species occur when one species affects another species' evolution via its effects on the abundance and traits of a shared partner species. What happens if those two species enact opposing effects on their shared partner's population growth? Furthermore, what if those two kinds of interactions involve separate traits? For example, many plants produce distinct suites of traits that attract pollinators (mutualists) and deter herbivores (antagonists). Here, we develop a model to explore how pollinators and herbivores may influence each other's interactions with a shared plant species via evolutionary effects on the plant's nectar and toxin traits. The model results predict that herbivores indirectly select for the evolution of increased nectar production by suppressing plant population growth. The model also predicts that pollinators indirectly select for the evolution of increased toxin production by plants and increased counterdefenses by herbivores via their positive effects on plant population growth. Unless toxins directly affect pollinator foraging, plants always evolve increases in attraction and defense traits when they interact with both kinds of foragers. This work highlights the value of incorporating ecological dynamics to understand the entangled evolution of mutualisms and antagonisms in natural communities.